Paul and the Galatians as “Children” of Abraham - Eschner, Christina (Parting of the Ways, 2024)
Many scholars argue that according to Paul, Christ had overcome and abolished the Law, so the “Parting of the Ways” already began with the apostle. They also interpret Gal 3–4 in this way. However, in this passage Paul is not concerned with the Law as such but with the soteriological role of the Law in particular. The central question is this: who belongs to the children of God and thus to those who gain righteousness and salvation? Paul rejects any relevance of the Law. Faith is the only criterion. This has always been true – also for Judaism. For Paul it is therefore faith that upholds the continuity between Judaism and Christianity in the history of salvation. Thus, with regard to the function of the Law, Paul deviates from the view that was widespread in ancient Judaism. Yet with respect to the actual practice of the Law, believers in Christ and Jews can be seen to coexist for a longer period of time.<br